COACHING CLIMATE: ITS IMPACT ON STUDENTS' MENTAL HEALTH IN EDUCATIONAL SETTINGS - Apsyati, Suci Pratita; Fitri, Mustika; Williyanto, Septian; Apriady, Hilmy; Rahman, Dally; Ockta, Yovhandra (JETL (Journal of Education, Teaching and Learning), 2024)
This research aims to investigate the relationship between mental health and motivation climate among coaches, considering gender differences. Although sports psychology among coaches is increasingly recognized as an essential element in athlete performance, research examining mental health and motivation climate among coaches remains limited. The study was conducted by administering questionnaires to 40 sports coaches, comprising 20 male coaches and 20 female coaches, active in various sports disciplines. The questionnaire was designed to assess the level of mental health and coaches' perceptions of the motivation climate created within the training environment. Statistical analysis results indicate that there is no significant correlation between mental health and the motivation climate created by coaches, both for male and female coaches. However, an interesting finding is that coaches' mental health has a greater influence on their performance than motivation climate. The implications of this research highlight the need for greater attention to coaches' mental health in efforts to enhance their performance. A better training environment can be created by considering coaches' mental well-being, which in turn will positively impact the motivation and performance of the athletes they coach. Additionally, this research also contributes to the literature on sports psychology, particularly in the context of sports coaching. In conclusion, this study demonstrates that coaches' mental health plays a crucial role in their success in coaching athletes, while the motivation climate created by them may not have the same significant impact. A better understanding of these dynamics can assist in the development of more effective strategies and programs to enhance coaches' well-being and the performance of the athletes they coach.